Phylogenetic analysis of mitochondrial 12S ribosomal RNA gene sequence of Mongolian wild boars - Khamit, Ali; Gun-Aajav, Bayarmaa; Dashzeveg, Oyuntsetseg; Batsuuri, Shinebayar; Shiikhar, Enkhmaa; D, Bayarlkhagva (Proceedings of the Mongolian Academy of Sciences, 2018)
Specimens of Mongolian wild boar (Sus scrofa) from Arkhangai, Dornod, Zavkhan, Orkhon, Ovorkhangai, Selenge, Tuv, Khovd, Khuvsgul and Uvs aimags (provinces) were subjected to DNA sequencing. Determined sequences from 18 specimens were registered into the GenBank and accession numbers were obtained. In this study mitochondrial 12S rRNA gene sequences of Mongolian wild boars were analyzed with 36 complete sequences of 12S rRNA gene of wild boar (Sus scrofa) available at NCBI GenBank. Sequence alignment, detection of parsimonious informative sites, model selection, calculation of nucleotide distances and tree construction with 1000 bootstrapped replications were conducted using MEGA 6. Maximum likelihood trees were constructed by the HKY model. A maximum likelihood tree with 53 complete sequences of mitochondrial 12S rRNA gene of Sus scrofa was constructed. Mongolian sequences from the same and adjacent locations were clustered together. European sequences were clustered together, additionally two sequences from south western China and two sequences from south eastern China were also clustered. Additionally, 12S rRNA gene sequences of Mongolian Sus scrofa, located between Asian and European sequences suggesting geographical location of Mongolia, played an important role in the gene flow between Asian and European wild boar population.